Development and Validation of RP-HPLC Method for Simultaneous Determination of Metoprolol Succinate and Olmesartan Medoxomil in Bulk and Pharmaceutical Dosage Form - Matthew Olabemiwo, Ojeyemi; Mahesh, Pottabattula; Nageshwar Rao, A.B.N.; Jayathirtha Rao, V. (Asian Journal of Chemistry, 2012)
An accurate, precise and reproducible isocratic RP-HPLC method was developed and subsequently validated for the analysis of metoprolol succinate and olmesartan medoxomil in bulk and tablet dosage forms. Method development was carried out on Agilent Eclipse XBD-C18 (5 μm, 150 mm × 4.6 mm I.D.) column. The mobile phase was a mixture of acetonitrile and buffer (10 mM KH2PO4) in the ratio of 70:30 v/v. The pH of the buffer was adjusted to 2.75 with orthophosphoric acid. The flow rate was set at 0.6 mL/min and UV detection at 225 nm. The retention time of metoprolol succinate and olmesartan medoxomil were found to be 2.233 and 3.000 min, respectively. Validation parameters such as linearity, accuracy, precision and robustness, limit of detection (LOD) and limit of quantification (LOQ) were evaluated for the method according to the International Conference on Harmonization (ICH) Q2 R1 guidelines. In the linearity study, the regression equation for metoprolol succinate and olmesartan medoxomil were found to be y = 68402x + 64710 and y = 110194x + 8855.3. Correlation coefficient was 0.9990 and 0.9996 for metoprolol and olmesartan, respectively. The proposed method is highly sensitive, precise, accurate, rapid and easy to perform and hence was successfully applied for the quantification of bulk and active pharmaceutical present in tablet dosage form.